Liminality and Urban Acceptance: A Case of Majnu ka Tilla, Delhi - Arpita Dayal; Leon A. Morenas (International Journal of Urban Design and Development, 2024)
This paper recognizes liminality as an important urban phenomenon that has an impact on lived experiences in the city. Looking through the lens of liminality allows an incorporation of a multilayered and processual approach that recognizes the in betweenness and ambiguities in the urban. To do so, the Tibetans exile community settlement of Majnu ka Tilla in Delhi, identified to be in a state of permanent liminality that is embedded in their practices of protractedness, is studied. Through an ethnographic research of the settlement, aspects of their lived experiences are examined to look into the political and cultural constructions of spatiality. Findings from the case study suggest that the indeterminate factors of their existence after forced exile have effectuated into a strong cultural resilience led gentrification despite the constant urge for urban acceptance and diffusion, both on paper and in society. This liminality has created a unique paradoxical coexistence of standing out yet urging to blend in, that has significant impact on its growth and identity patterns with respect to the rest of the city. In conclusion, the paper argues that a liminal perspective on complex urban situations provides a more holistic insight into the ambivalence between social, cultural and political relationships, at the threshold of the dualities that usually govern normative urban design praxis and theory.
Keywords: Liminality; Tibetan exile community; Urban design theory; Urban spaces